TENSES USAGE IN BEAR’S MAGIC MOON STORY BOOK - Retno Budi Astuti (Jurnal Sosial Humaniora dan Pendidikan, 2024)
Grammar is taught to all language learners as one of the components of the English language. This research is conducted to find out the usage of tenses in children’s book entitled Bear’s Magic Moon written by Suzanne Pinner as children start to learn about language. The tenses theory from Betty Schrampfer Azar is used for the classification of the tenses. The method that is used in this research is qualitative research method. As the result, the researcher found that there are 30 data for the simple present tense, 1 data for the simple past tense, and 4 data for the simple future tense. The simple present tense is used in most of the sentences and the simple past tense are the least used in the sentences of the book.